Developing a tool for process‐oriented appraisals and rewards: Design science research. Issue 3 (4th October 2020) - Shafagatova, Aygun; Van Looy, Amy
Abstract: While business process management (BPM) has become a recognized discipline, managers are still challenged to achieve an appropriate alignment between BPM their BPM needs and other management practices in the organization. Specifically, the aligned behavior and performance of employees and teams are crucial to reap the full benefits of BPM. To help managers face such alignment challenges, we have developed a qualitative decision support tool, called "process‐oriented appraisals and rewards" (POAR), by combining design‐science research with a strong qualitative approach. Our study contributes to the BPM and human resource management (HRM) disciplines by extending multifaceted knowledge, while also offering a practical tool for managers to support their decision making regarding a BPM‐HRM alignment. Abstract : We introduce a qualitative management tool, called POAR (process‐oriented appraisals and rewards), that facilitates structured brainstorming exercises between managers to align their business process management and human resource appraisals and rewards practices. The tool integrates all necessary knowledge, guidance, components, and alignment steps in a single instrument. For the purpose of tool development, we conducted a design‐science research (DSR) study.